2015
DOI: 10.1016/j.jhevol.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Humeral torsion and throwing proficiency in early human evolution

Abstract: BackgroundIn their recent paper, "Clavicle length, throwing performance and the reconstruction of the Homo erectus shoulder," Roach and Richmond (2015) test the hypothesis that relative clavicular length predicts scapular position and explore whether or not variation in relative clavicular length in a sample of modern humans from northwestern Kenya is correlated to throwing performance. Since the impetus to undertake these analyses is in part based on supposed claims I have made in my research on hominin shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
33
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 50 publications
5
33
1
1
Order By: Relevance
“…We further concluded that the data better support the presence of modern human-like, laterally facing shoulders dating back to H. erectus or earlier. Larson (2015) does not agree with our conclusions or with the way we present her research.…”
Section: Introductioncontrasting
confidence: 76%
See 4 more Smart Citations
“…We further concluded that the data better support the presence of modern human-like, laterally facing shoulders dating back to H. erectus or earlier. Larson (2015) does not agree with our conclusions or with the way we present her research.…”
Section: Introductioncontrasting
confidence: 76%
“…Given that relative clavicle length is both the only data support for the anterior shoulder model and the primary logic behind it, understanding the clavicle is clearly the key to evaluating Larson's hypothesis. Larson (2015) suggests that our summary of her work conflates what anatomical factors are causes and what are effects. We have not proposed any hypotheses about cause and effect.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations